Computational studies on amino-type excited-state intramolecular proton transfer and subsequent cis–trans isomerisation reactions of three 2-(2'-aminophenyl)benzothiazole derivatives. (1st February 2017) - Zhu, Qiuling; An, Beibei; Yuan, Huijuan; Li, Yuanyuan; Guo, Xugeng; Zhang, Jinglai
ABSTRACT: Excited-state intramolecular proton transfer (ESIPT) reactions of three amino-type 2-(2'-aminophenyl)benzothiazole (PBT-NH2 ) derivatives, that is, 2-(2'-methylaminophenyl)benzothiazole (PBT-NHMe), 2-(2'-acetylaminophenyl)benzothiazole (PBT-NHAc) and 2-(2'-tosylaminophenyl)benzothiazole (PBT-NHTs), have been explored by the time-dependent density functional theory (TD-DFT) method with the B3LYP density functional. In addition, their absorption and fluorescence spectra were also simulated at the same theoretical level. The present studies reveal that the energy barriers of the first singlet excited state of the three titled compounds along the ESIPT reactions are predicted at 0.39, 0.30 and 0.12 eV, respectively, suggesting that the inclusion of a strong electron-withdrawing tosyl group can remarkably facilitate the occurrence of the ESIPT reaction, while the involvement of an electron-donating methyl group has no effect on the ESIPT process of the amino-type hydrogen-bonding system. Following the ESIPT, both PBT-NHAc and PBT-NHTs molecules can also undergo the cis – trans isomerisation reactions along the C2 –C3 bond between benzothiazole and phenyl moieties, in which the energy barriers of the trans -tautomer → cis -tautomer isomerisations in both ground states are calculated at 0.33 and 0.27 eV, respectively. This implies that there may exist a long-lived trans -tautomer species in the ground states for PBT-NHAc and PBT-NHTs, as observed in the spectroscopic experiments of PBT-NHTs. Abstract :